Beobachtungen zum Casiquiare-Problem - Besler, Helga (ERDKUNDE, 1995)
In spring 1992 I had the opportunity to follow ALEXANDER VON HUMBOLDTS famous itinerary in South America from the Rio Negro to the Orinoco River through the Casiquiare Canal. The very low water level allowed new observations on the river banks and channel bed. Their changing characters are briefly summarized and discussed. From this evidence, STERNS theory of the Casiquiare formation is questioned. A new explanation is offered, suggesting that the lower and middle Casiquiare, including all eastern tributaries had been tributary to the Orinoco and that slight tectonic movements (uplift between the R. Pamoni and R. Guramoni, and relative downwarp near the Rio Negro) caused the capture of the Casiquiare near the inselberg east of San Carlos where the former watershed had been (Fig. 1). Thus, the present situation is just one stage in river capture where reversing of a tributary usually leads to the truncation of the whole river system (in this case the Orinoco).